AI-Powered Simulation and Virtual Reality in Medical Training: Current Trends and Future Prospects - Srivastava, Nandini; Shah, Darshan Dipakbhai; Srivastava, Vijay Kumar; Chhajwani, Sunil; Patel, Jitendra (Medical Science: Trends and Innovations Vol. 12, 2025)
The integration of Artificial Intelligence (AI) and Virtual Reality (VR) in medical training has revolutionized the learning experience by providing immersive, interactive, and adaptive simulations. AI-powered VR platforms enable personalized training, real-time feedback, and risk-free environments for skill acquisition, making them valuable tools for medical education and surgical practice. This review explores the current advancements in AI-driven VR simulations, including their applications in clinical skills training, patient management, and surgical procedures. Additionally, the challenges associated with implementation, such as cost, accessibility, and ethical considerations, were analyzed. The future prospects of AI in medical training are also discussed, highlighting potential innovations such as haptic feedback integration, natural language processing for virtual patient interactions, and AI-driven assessment tools. AI-powered VR simulations are poised to bridge the gap between theoretical knowledge and practical expertise, transforming the future of medical education.